Empowering sharia-based Micro, Small and Medium Enterprises (MSMEs) in Indonesia: A Socioeconomic and ethical framework for inclusive development - Rukmanda, Meirani Rahayu; Bisri, Hasan; Jubaedah, Dedah; Gojali, Dudang; Hadi, Sholikul (International Journal of Nusantara Islam, 2025)
Sharia-based Micro, Small, and Medium Enterprises (MSMEs) represent a critical driver of economic development in Indonesia, contributing significantly to employment, poverty alleviation, and local entrepreneurship. In a country with the world’s largest Muslim population, the integration of maqāṣid al-sharī‘ah principles into MSME governance offers a unique pathway toward ethical and inclusive economic growth. This study investigates the institutional, financial, and socio-religious dynamics that shape the performance and sustainability of Sharia-compliant MSMEs. It explores how Islamic economic principles intersect with regulatory frameworks and market practices to influence business outcomes in this sector. The objective is to formulate a conceptual and practical model for strengthening Sharia-based MSMEs in Indonesia. Adopting a qualitative approach, this research utilizes document analysis from regulatory texts, journal articles, and Islamic economic theory. Findings reveal critical challenges in legal harmonization, limited access to Sharia-compliant financing, and inconsistent application of ‘adl (justice), amanah (trust), and raḥmah (compassion) in entrepreneurial practices. However, notable opportunities exist in the areas of community-based empowerment, halal certification, and fintech adoption aligned with Islamic values. This study contributes to both policy and academic discourses by offering an integrative perspective on Sharia-based MSMEs. It highlights the importance of strengthening tawhidic foundations in economic structures and provides a roadmap for policymakers, practitioners, and scholars committed to building an inclusive and just economic system rooted in Islamic ethics.